Peran media sosial dalam membangun personal branding wirausahawan - Nova, Mellynda Az Zahra (Maliki Interdisciplinary Journal, 2025)
Personal branding is an important factor in the increasingly competitive business world, where an entrepreneur’s self-image can influence the trust of customers and business partners. In this case, social media plays a crucial role as a tool to shape and spread this image widely and quickly. This article discusses how social media helps increase visibility, build credibility, and expand business networks effectively. With the right strategy, entrepreneurs can utilize various digital platforms to build a strong identity, actively communicate with customers, and understand changing market trends. However, challenges such as negative comments, hoaxes, and reputation crises remain threats that must be managed carefully. With a consistent approach, personal branding can be maintained sustainably through social media.